Soil test based nutrient management on garden pea (var. Arkel) under paddypea cropping sequence at wokha district in Nagaland - Ray, S. K. (Indian Journal of Hill Farming, 2015)
A frontline demonstration on soil test based nutrient management (STBNM) on garden pea was carried out during the post kharif season in 2013 at six villages in Wokha District in Nagaland. The average green pod yield of nutrient management plots for pea were 3.95 to 5.53 t ha-1 and yield increased by 49.11 to 63.65% as compared with farmers practice/control plots. The nutrient management plots also gave higher gross returns (Rs/- 47,436.00 to Rs/- 66,396.00) and net returns (Rs/-21,836.00 to 40,496.00) compared to the farmers practice plots which gave Rs/- 24,120.00 and Rs/-9,120.00, respectively.